Estrogen signaling as a bridge between the nucleus and mitochondria in cardiovascular diseases - Guajardo-Correa, Emanuel; Silva-Agüero, Juan Francisco; Calle, Ximena; Chiong, Mario; Henríquez, Mauricio; García-Rivas, Gerardo; Latorre, Mauricio; Parra, Valentina (Frontiers in Cell and Developmental Biology, 2022)
Cardiovascular diseases (CVDs) are the leading cause of morbidity and mortality worldwide. Epidemiological studies indicate that pre-menopausal women are more protected against the development of CVDs compared to men of the same age. This effect is attributed to the action/effects of sex steroid hormones on the cardiovascular system. In this context, estrogen modulates cardiovascular function in physiological and pathological conditions, being one of the main physiological cardioprotective agents. Here we describe the common pathways and mechanisms by which estrogens modulate the retrograde and anterograde communication between the nucleus and mitochondria, highlighting the role of genomic and non-genomic pathways mediated by estrogen receptors. Additionally, we discuss the presumable role of bromodomain-containing protein 4 (BRD4) in enhancing mitochondrial biogenesis and function in different CVD models and how this protein could act as a master regulator of estrogen protective activity. Altogether, this review focuses on estrogenic control in gene expression and molecular pathways, how this activity governs nucleus-mitochondria communication, and its projection for a future generation of strategies in CVDs treatment.